Utilitarian Justice in the Decision of the Land Exchange Agreement: A Case Study of Decision Number 241/Pdt.G/2016/Pn.Smn Reviewed from the Post-Positivism Paradigm - Muhammad Syahri Ramadhan; Yuli Prasetyo Adhi; Rahayu Fery Anitasari (Universitas Negeri Semarang, 2025)
The Sleman District Court Decision Number 241/Pdt.G/2016/PN.Smn, which recognizes the validity of non-formal land exchange agreements, constitutes a significant case for understanding the realization of substantive justice beyond a positivistic legal framework. This study analyzes the decision using Jeremy Bentham’s utilitarianism approach within the post-positivist paradigm developed by Guba and Lincoln. Employing a normative legal research method with a case-based analytical approach, this research demonstrates that the judges did not merely assess the formal legality of the agreement but also took into account social consequences, practical benefits, and empirical realities existing within the community. Utilitarianism is applied to evaluate the extent to which the decision maximizes overall happiness and minimizes suffering for the disputing parties as well as society at large. Furthermore, post-positivism provides an epistemological framework that conceptualizes law as a contextual, non-final, and socially constructed phenomenon open to reinterpretation. The findings suggest that this combined approach yields a more responsive, flexible, and socially meaningful form of justice, while also generating significant methodological implications for research on non-formal agreements, particularly through the use of qualitative methods, data triangulation, and hermeneutical interpretation.